Development of Solid State Reference Electrode Based on Polypyrrole (PPy) and Screen Printed Electrode (SPE) - Alva, Sagir; Asadullah, Masud; Friliandita, Vivi; Khaerudini, Deni Shidqi (Universitas Syiah Kuala, 2023)
In this study, a Polypyrrole doped KCl/KCl saturated (PPy-Cl/KCl) reference electrode had been successfully developed. In this development process, the PPy-Cl/KCl reference electrode that had been provided consisted of two stages of refinement, specifically the PPy-Cl/KCl 1 reference electrode which became the PPy-Cl/KCl 2 reference electrode. Furthermore, the PPy-Cl/KCl 2 SRE was made into 3 types with cycle variations of 10, 15, and 20 cycles and the mV response value test and Scanning Electron Microscopy (SEM) test were carried out. Regarding the variation results, PPy-Cl/KCl 2 SRE was obtained with 15 cycles as the best PPy-Cl/KCl 2 reference electrode with mV value of 3.43 mV. Subsequently, the PPy-Cl/KCl 2 SRE with 15 cycles was involved in the characterization test using cyclic voltammetry (CV) testing, response testing vs Cl sensors and drift testing. In the CV testing, the PPy-Cl/KCl 2 SRE with 15 cycles indicated a voltammogram graphic pattern similar to the Ag/AgCl reference electrode as a commercial reference electrode. Moreover, in the response testing vs the Cl sensor, the PPy-Cl/KCl 2 SRE with 15 cycles provided a Nernstian number value of -54.5 mV/s with a testing range of 0.1-104 M, and in the PPy-Cl/SRE drift testing, KCl 2 with 15 cycles indicated fairly good stability, particularly with a drift value of 1 mV/minute which was achieved after the conditioning process after 3.5 minutes.